Analisis Pengaruh Digital Marketing, Komunikasi Pemasaran dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pengguna IPhone - Chandra, Johnny (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research analyzes the influence of digital marketing, marketing communications, and service quality on consumer satisfaction. The population in this research is iPhone user consumers. This research uses a purposive sampling method. The method is based on criteria with a sample size of 100 respondents. The model used in this research is multiple linear regression analysis. The partial research results show that digital marketing variables have a positive and significant effect on consumer satisfaction. Marketing communication has a positive and significant effect on consumer satisfaction. Service quality has a significant negative effect on consumer satisfaction. The results of simultaneous research tests show that digital marketing, marketing communications and service quality have a positive and significant effect on consumer satisfaction. The results of this research obtained an Adjusted R Square value of 69.1%. The remaining 30.9% can be explained by other variables outside this research, for example Web E-Commerce, promotions and others.